Development of A Holistic Assessment Instrument Based on Computer Based Test on Environmental Pollution Learning - Rusdiyanto, Dini Rosdiane; Rubini, Bibin; Permana, Irvan (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to develop a holistic assessment instrument based on Computer Based Test (CBT) that meets the criteria of good assessment in the context of learning Environmental Pollution in Junior High School, especially grade VII. The research method used is Research and Development (R&D) with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The assessment instrument consists of 30 multiple-choice test items that cover the dimensions of knowledge, attitudes, communication skills, and collaboration skills. The development of questions through the process of item content validity and media validity validated by two competent experts each, peer science teachers and students. The obtained data is then analyzed using: product moment correlation, the Kuder-Richardson-20 (KR-20) formula, the Du Bois formula, and the item discrimination index. Based on the results of item analysis, 26 questions were tested valid and reliable with a reliability score of 0.862. The results of the difficulty test showed 69.23% of the questions were quite difficult, 11.54% of the questions were too difficult, and 19.23% of the questions were too easy. The differentiating power test showed 61.54% of the questions had good differentiating power and 38.46% of the questions were in the sufficient category. Based on these results, the instrument developed has the potential to increase the effectiveness of learning Environmental Pollution in Junior High School, especially grade VII and provide comprehensive information about student achievement in various dimensions of learning.